Nickel centered metal-organic complex as an electro-catalyst for hydrogen evolution reaction at neutral and acidic conditions. (7th February 2020) - Rajakumar, Madhumitha; Manickam, Matheswaran; Gandhi, Nagarajan Nagendra; Muthukumar, Karuppan
Abstract: In this study, we report the development of dihydropyrimidines substituted nickel electro-catalyst at mild conditions for hydrogen evolution reaction. The Biginelli type reaction was carried out to produce 4-(4-chlorophenyl)-3, 4, 5, 6-tetrahydrobenzo[h]quinazoline-2(1H)-thione moiety. This was added with NiCl 2 .6H 2 O to synthesize Ni-quinazoline-2(1H)-thione catalyst. The prepared catalyst was characterized using UV–Vis, FT-IR, Mass, 1 H and 13 C NMR and SEM-EDX spectroscopy. It showed an excellent hydrogen evolution reaction (HER) activity. LSV polarization showed a low Tafel slope (34 mV/dec) nearly close to Pt/C (28 mV/dec) in neutral medium whereas a Tafel slope of 100 mV/dec was observed with 0.5M H2 SO4 while Pt/C showed 50 mV/dec. Electrochemical impedance spectroscopy measured by applying −1.18 V in neutral medium showed two depressed semicircles whereas with 0.5M H2 SO4 and -1.45 V applied voltage single half was observed. Highlights: Dihydropyrimidines substituted nickel electro-catalysts were synthesized and characterized. Catalyst showed excellent hydrogen evolution reaction (HER) activity. Low Tafel slope indicated that the reaction follows Volmer-Heyrovsky mechanism.